Infectious mononucleosis – should we routinely assess liver function in acute presentation and follow up?. Issue 3 (25th March 2023) - Simpson, L; Sutherland, E; Wilkinson, D; Saman, R; Edafe, O
Abstract: Objective: Infectious mononucleosis is a relatively common acute presentation to the ENT department. There is an expected derangement in the liver function test results in most patients. There is no guidance regarding follow up, and practice varies. This study aimed to evaluate the utility of liver function tests and abdominal ultrasound in infectious mononucleosis. Methods: This was a retrospective study of all adult patients admitted under ENT with infectious mononucleosis over a five-year period. Results: A total of 153 patients were included; 80 per cent had abnormal liver function test results at presentation. Around 50 per cent had at least one liver function test assessment following discharge. Median (interquartile range) time to resolution of liver function test results was 32 days (20–50 days); maximum time was 10 months. Six patients had in-patient abdominal ultrasound: all showed a normal liver and biliary tree. No patient developed any liver disease sequelae. Conclusion: The findings suggest that serial assessment of liver function is not required in immunocompetent adults with subclinical derangement in liver function.